1998
DOI: 10.1016/s0008-6363(98)00115-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ventricular pacing-induced tachycardia on aortic mechanics in man

Abstract: Pacing-induced increases in pulse frequency may result in improved aortic distensibility and aortoventricular coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
49
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 15 publications
8
49
0
4
Order By: Relevance
“…It should be noted, however, that the reproducibility of Tr has been reported to be fair to good (ICC: 0.43-0.84) 2, 13, 14) , and, given the low sample size of the two aforementioned studies (n = 20 and 22, respectively), these findings must be interpreted with caution. Stefanadis et al (1998) reported reduced local aortic stiffness and increased distensibility during incremental ventricular pacing 35) , which stands in further contrast to the results of similar or increased stiffness reported by Wilkinson 10, 11) and Lantelme 34) . Conversely, an observational study (n = 253) reported that a high HR is strongly associated with reduced carotid artery distension and an elevated aortic pulse wave velocity, even after adjusting for age and blood pressure 36) .…”
Section: Variables Influencing the Aixmentioning
confidence: 60%
“…It should be noted, however, that the reproducibility of Tr has been reported to be fair to good (ICC: 0.43-0.84) 2, 13, 14) , and, given the low sample size of the two aforementioned studies (n = 20 and 22, respectively), these findings must be interpreted with caution. Stefanadis et al (1998) reported reduced local aortic stiffness and increased distensibility during incremental ventricular pacing 35) , which stands in further contrast to the results of similar or increased stiffness reported by Wilkinson 10, 11) and Lantelme 34) . Conversely, an observational study (n = 253) reported that a high HR is strongly associated with reduced carotid artery distension and an elevated aortic pulse wave velocity, even after adjusting for age and blood pressure 36) .…”
Section: Variables Influencing the Aixmentioning
confidence: 60%
“…[40][41][42] There was also a contradictory study showing reduced aortic stiffness and increased distensibility during incremental pacing. 43 Therefore, in order to clarify the relationship between arterial distensibility and heart rate, and its pathophysiology, further specific studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the effects of heart rate manipulation reported by Morelli et al [2] differed from data observed in middle-aged healthy individuals [8]. Using central measurements of aortic pressure and volumetric catheters to determine aortic volume, Stefanadis et al [8] observed that pacing did not affect MAP, decreased systolic blood pressure while diastolic pressure was increased, and decreased the augmented pressure (the difference between central and peripheral systolic pressure).…”
mentioning
confidence: 92%
“…Using central measurements of aortic pressure and volumetric catheters to determine aortic volume, Stefanadis et al [8] observed that pacing did not affect MAP, decreased systolic blood pressure while diastolic pressure was increased, and decreased the augmented pressure (the difference between central and peripheral systolic pressure). Interestingly, distensibility of the aorta increased and stiffness index decreased at high HR, indicating that Ea should decrease at high HR.…”
mentioning
confidence: 99%